O contradiscurso de resistência feminista em interações online: estratégias no combate ao antifeminismo - Abreu, Sergiana Cortez de (2020)
Feminism is a movement historically marked by resistance. Currently, this movement has gained strength and representativeness and human interaction, through social networks, plays an important role in this process, as these networks qualify as powerful tools of aggregation, interaction and information. However, with the increase in hate speech on the web, Feminism and feminists have been the target of social stigmas, prejudices and actions that diminish the movement's identity and try to silence the movement's militants. As a result, the aim of our research is to analyze feminist linguistic-discursive strategies to combat anti-feminist hate speech. The theoretical bases that founded it come from the Critical Discourse Analysis of Fairclough (2011), focusing on the three-dimensional model, which understands the discourse as a social practice, a way of the subject's action on the world and on others through representations and meanings of that world. Furthermore, we are supported by Bakhtin's (2003,2006) dialogism to understand the responsive role of feminists in the face of hate speeches that mobilize conflicting ideologies to the ideal defended by the movement. For that, we chose as categories of research analysis: the intertextuality of Fairclough (2001), thetransitivity system of the LSF of Halliday (1994), the referential and sequential cohesion of Koch (1987, 2005, 2013, 2013a, 2014, 2017), the counter-argumentative structure of Adam (2008), the semantics of Fairclough (2001) and the polyphony of Bakhtin (2003). We took as a sample a corpus formulated by three (re) posts and seventeen feminist comments, all from the Empodere two women fanpage collected in 2018. The methodology used to enable the generation and analysis of the data was to mobilize an ethnographic case study qualitative / interpretative in nature. For this, initially, we analyzed the context of the movement's struggle. Next, we interpreted intertextuality and polyphony in the process of production, distribution and consumption of discursive practices to combat ideologies contrary and / or divergent to that advocated by Feminism, while explaining the ideologies that emerged from these discourses forged by feminists. Finally, we describe the textual resources mobilized for the consolidation of feminist counter arguments. The analyzed data revealed the resistance of feminist discursive practice to defend a definition of the movement through personal experiences and opinions on selected excerpts from hate speech, in addition to using empathetic, tolerant and inclusive speeches. During this process, Feminism had its image associated with the idea of freedom, respect, equality, female empowerment and the struggle for the will of women. In addition, the argumentative basis was forged in denouncing structural machismo. These results allow us to affirm that feminists practice a resilient counter-discourse in the face of anti-feminist subjects and the contrary and prejudiced ideologies that emerged from hate speech. Thus, the data show that the fight against anti-feminist hate speech is a social practice of ideological deconstruction of the oppressive power structures present in society and that shape and influence the hate speech to the movement.